If it's not what You are looking for type in the equation solver your own equation and let us solve it.
8g+6=1-2g
We simplify the equation to the form, which is simple to understand
8g+6=1-2g
We move all terms containing g to the left and all other terms to the right.
+8g+2g=+1-6
We simplify left and right side of the equation.
+10g=-5
We divide both sides of the equation by 10 to get g.
g=-0.5
| x^2-22x-15=0 | | y=(-2x)+7 | | y=(-2)+7 | | -9+x=x-8-23 | | 6x+42=90 | | 1/5x=2/5 | | 4R-1=2R+9 | | 8p^2-53p-56= | | x-20=35x-20 | | 8p^2-53p-56p= | | x=12-5x | | 25-15=5(x-3) | | 3a+2b=30a | | 5x+30/20 | | 28=9x+4-5x | | 140,000/1130 | | 5x^3+4x^2+4x=0 | | 15n^2-32np-7p^2= | | 41-n=-21 | | (3cosx-1)-4=0 | | 11/12x100 | | x^1/3=5 | | x/35=7/15 | | 28=9x+4.5x | | x^1/2=6 | | 35w^2-44wz-7z^2= | | 3+n/18=4 | | [-2+(-5)]+[3+(-1)]= | | x-3+4=+x-6 | | -4b=4b | | 3.1=8.5-0.6x | | -3(5-t)=12 |